#### Answer

Solution: $(-12,-5)$
(checked below)

#### Work Step by Step

Step 1
Solve one of the equations for one of the variables.
Select the first equation as the x has a coefficient of -1.
$ 2=2y-x\qquad$ ... add $x-2$
$x=2y-2$
Step 2
Substitute $2y-2$ for $x$ in the other equation and solve for $y$
$ 23=5y-4(2y-2)\qquad$ ... (distribute, simplify)
$ 23=5y-8y+8\qquad$ ... add $-8$, simplify
$ 15=-3y\qquad$ ... divide with -3
$y=-5$
Step 3
Substitute $-5$ for $y$ in $x=2y-2$.
$x=2(-5)-2$
$x=-12$
Solution: (x,y) = $(-12,-5)$
Check: $\left[\begin{array}{lll}
2\stackrel{?}{=}2(-5)-(-12 & ..... & 23\stackrel{?}{=}5(-5)-4(-12)\\
2=-10+12 & & 23=-25+48\\
2=2 & & 23=23\\
& &
\end{array}\right]$